The incidence and quality of graphs in annual reports: a South African analysis of graph disclosure in state-owned enterprises - Kathrada, Anees Fareed (My University, 2020)
Recent accounting scandals involving VBS Mutual Bank, the Steinhoff retail group and alleged Gupta-related companies have brought the accounting profession into disrepute and created doubt about the adequacy of South Africa’s principles of corporate governance and the application of corporate reporting principles. The annual report has become one of the most important ways in which companies communicate with their stakeholders. The format of the annual report has undergone changes over time due to the demands stakeholders have placed on companies to provide a holistic view of the company. There has been an increased use of visual content in corporate reporting. The purpose of this study was to analyse the incidence, quality and measurement distortion of graphs in the annual reports of South African state-owned entities for the financial year ending 2018. Impression management theory, in its original form, considers the actions of individuals performing for an audience to create desired perceptions. Management may attempt to portray a more favourable impression and thus use graphs as a tool to manipulate information and at the same time deceive readers. State-owned entities are accountable to various stakeholders such as parliament and its oversight committees, the government and government agencies, external monitoring parties such as credit-rating agencies, investors and creditors and the public and its special interest groups. This research paper aims to fill the gap in current literature as no research of this nature has been done in the public sector to the author’s knowledge. The research adopted a descriptive quantitative research approach. The research examined the use of graphs by state owned entities in terms of the extent of graph use, the nature and type of graphs used, compliance with good graph standards and the measurement distortion of graphs.The findings indicated that 64% of South African state-owned entities presented graphs in their annual report indicating the prevalence of the usage of graphs, with non-financial graphs being disclosed much more when compared to financial graphs. In terms of measurement, South African state-owned entities tend to overstate data trends more than understating trends. This was measured using the Graph Discrepancy Index. Presentational enhancement was however noted as not as prevalent. Graphs therefore appear to be used as a form of impression management to manage stakeholder’s perceptions of state-owned entities
A research report submitted In partial fulfilment of the requirements for the degree of Master of Commerce, University of the Witwatersrand, 2020